Mixed Plantation for Effective Soil Conservation in the Nilgiris - Agarwal, S. C.; Chinnamani, S.; Rege, N. D. (Indian Forester, 1961)
Extensive plantations of Eucalyptus globulus and Acacia mollissima have been taken up in the Nilgiris and Kodaikanal as a planned Forestry measure. Experiments laid down at the Central Soil Conservation Research Station have indicated that Eucalyptus globulus even at an espacement of 6’Ã— 6’ permits a fairly heavy soil loss, even though the leaf litter was allowed to accumulate. From the fourth year onwards the soil loss was not experienced at this espacement. It is seen that in bigger and older plantations of bluegum the leaf is invariably collected for oil, the humus is poor and very often rills and gullies appear. Moreover this species is lopped very heavily for oil.